2022
DOI: 10.1101/2022.03.31.486566
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Establishment of a social conditioned place preference paradigm for the study of social reward in female mice

Abstract: Social interactions can be and often are rewarding. The effect of social contact strongly depends on circumstances, and the reward may be driven by varied motivational processes, ranging from parental or affiliative behaviors to investigation or aggression. Reward associated with nonreproductive interactions in rodents is measured using the social conditioned place preference (sCPP) paradigm, where a change in preference for an initially neutral context confirms reinforcing effects of social contact. Here, we … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The finding that sCPP can be elicited in adult mice using contact with age and sex matched conspecifics as a reward appears contradictory to the previous findings by Nardou and collaborators in 2019, who have shown that sCPP was no longer observed at the age of 8 weeks in male, and at 11 weeks in female mice 35 . However, in the study the short (2 days) conditioning protocol was used 35 , and we have recently shown that sCPP can be observed in adult (>11 weeks) female mice, when the longer, 6-day, conditioning protocol is used 34 . Here, to assess if the effect of conditioning length is similar in males, we performed additional experiment on male mice using a 2-day conditioning protocol ( Fig.2D-E, Table S5-S6 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The finding that sCPP can be elicited in adult mice using contact with age and sex matched conspecifics as a reward appears contradictory to the previous findings by Nardou and collaborators in 2019, who have shown that sCPP was no longer observed at the age of 8 weeks in male, and at 11 weeks in female mice 35 . However, in the study the short (2 days) conditioning protocol was used 35 , and we have recently shown that sCPP can be observed in adult (>11 weeks) female mice, when the longer, 6-day, conditioning protocol is used 34 . Here, to assess if the effect of conditioning length is similar in males, we performed additional experiment on male mice using a 2-day conditioning protocol ( Fig.2D-E, Table S5-S6 ).…”
Section: Resultsmentioning
confidence: 99%
“…Two sets of conditioning contexts were used ( Table S13 ), and the results from both contexts were pooled. When the number of animals conditioned on different bedding types were not equal, the number of animals for each type of bedding was equalized by randomly removing the appropriate number of cases from the larger group using an R script as described in 34 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations